Pengolahan Limbah Cair Industri Minyak Sawit Menggunakan Reaktor Listrik Plat Kolom Secara Kontinu serta dengan Penambahan PAC - Dwi Widyaningsih; Idral Amri; Desi Heltina (Jurusan Teknik Kimia, Fakultas Teknik, UNRI, 2021)
Palm oil industrial waste contains various dissolved compounds in the form of short fibers, hemicellulose, and their derivatives, proteins, free organic acids, a mixture of minerals and organic pigments such as anthocyanins, carotenes, polyphenols, lignins and tannins. Organic compounds in this waste will cause problems such as an increase in TSS, COD values which can pollute the environment. The electrocoagulation method has the potential to reduce TSS, TDS, COD content and neutralize pH. The purpose of this study was to determine the effect and optimum conditions of the electrocoagulation process with variations in flow rate, voltage, spacing between plates and the addition of poly aluminum chloride (PAC) coagulants to decrease TSS, COD and pH parameters so that they meet the quality standards of waste in Permen LH. No. 5/2014. The method used is a continuous electrocoagulation process using an aluminum catalyst and the addition of PAC. The variables used in this study were the stress variable (24; 26; 28 V) and the variable flow rate velocity (0.3; 1,2; 2.5 L / min) and the variation of the spacing between the plates (2, 3, 4 cm). The results of this study found that the optimum conditions were obtained at a voltage of 28 volts and a flow rate of 0.3, and a distance between the plates of 2 cm and the addition of 400 ppm PAC with a percentage of TSS removal of 92.093% from 2150 mg / L to 170 mg / L, and a decrease in COD of 85.343% from 1310 mg / L to 192 mg / L. The results obtained show that it is in accordance with the standards of the Ministry of Environment and Forestry Regulation No.5 of 2014.